MUG303 : Popular music ensemble / College of Creative Arts - UiTM, College of Creative Arts (Universiti Teknologi MARA (UiTM), 2024)
This course introduces students to the terms, forms and styles of popular music. Students will be expected to recognize popular music forms and styles from listening, utilize proper popular music terms and to perform on their principal instrument in a popular music ensemble. The music that is to be performed will be chosen by the lecturer and will be dependent on the instrumentation of the present class.